2016
DOI: 10.15407/spqeo19.03.295
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of InSb p-n junctions prepared by diffusion methods

Abstract: Abstract. InSb p-n junctions were prepared by three diffusion methods, including isothermal, two-temperature and two-stage diffusion processes. The current-voltage characteristics were measured as a function of temperature and bias voltage. The highest values of the resistance-area product at zero bias have been obtained for the junctions prepared using the two-stage diffusion process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Further analysis of experimental data in InSb and InAs p-n junctions revealed that inhomogeneities are responsible for the tunneling current at both reverse and forward biases [2,3]. The possible reason for the higher concentration of extended defects in TR1 junctions may be retrograde solubility of cadmium in InSb [5].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further analysis of experimental data in InSb and InAs p-n junctions revealed that inhomogeneities are responsible for the tunneling current at both reverse and forward biases [2,3]. The possible reason for the higher concentration of extended defects in TR1 junctions may be retrograde solubility of cadmium in InSb [5].…”
Section: Resultsmentioning
confidence: 99%
“…where E 0 = 29 meV is the characteristic energy. Other parameters in the equation (1) are shown in Table [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before photoelectrical measurements, the samples were stored in isopropanol to prevent the effect of atmospheric moisture on the surface. Photodiodes were fabricated by the Cd diffusion at tem-peratures near 400 ∘ C. Fabrication details have been described earlier [10]. Direct current (DC) and highfrequency (1 MHz) capacitance measurements were used to characterize the photodiodes.…”
Section: Methodsmentioning
confidence: 99%